An Alternative to Desktop GIS? Evaluating the Cartographic and Analytical Capabilities of WebGIS Platforms for Teaching. (2nd April 2020) - Fast, Victoria; Hossain, Fahim
Abstract : The increasing prevalence of (open) geospatial data has amplified the demand for online tools to input, manage, and analyse data and generate cartographic outputs. WebGIS platforms are responding to this demand by delivering cost-effective, relatively easy to use compared to desktop GIS software, and increasingly sophisticated tools. The continued advancement of webGIS platforms highlights the necessary, but tricky, integration of these platforms into university curriculum. In this paper, we develop an evaluation framework for users to assess, compare, and benchmark the cartographic capabilities of four webGIS platforms–ArcGIS Online, Carto, Mapbox, and GIS Cloud–against standard GIS functionality. The webGIS platforms studied offer advanced data management and some spatial analysis capabilities, but in contrast, they have limited cartographic capabilities for creating static maps. Recognizing that platforms change, and change often, this study serves to benchmark the capabilities of webGIS platforms, while reflecting on the observed challenges to teaching neocartography tools.